Redox species and oxygen fugacity of slab-derived fluids: Implications for mantle oxidation and deep carbon-sulfur cycling - Li, Yi-Bing; Chen, Yi; Su, Bin; Zhang, Qing-Hua; Shi, Kai-Hui (Frontiers in Earth Science, 2022)
The generation and migration of slab-derived fluids modulate subduction zone seismicity, arc magmatism, and deep volatile cycling. However, the redox species and oxygen fugacity (fO2) (hereafter expressed as log units relative to the fayalite–magnetite–quartz buffer, △FMQ) of slab-derived fluids are highly debated. Here we conducted phase equilibria modeling on altered oceanic crust (AOC) and serpentinites along typical subduction geotherms in the C-S-bearing system over a pressure range of 0.5–6 GPa. With the averaged compositions of AOC and serpentinite, our calculated results show that oxidized carbon-sulfur species dominate slab-derived fluids during slab subduction. As a result, slab-derived fluids are highly oxidized and at or above the typical △FMQ values of arc magmas at forearc to subarc depths. The predicted oxidized carbon and sulfur species are compatible with natural observations in fluid inclusions from many oceanic HP metamorphic rocks. More importantly, it is revealed that, the redox state of slab-derived fluids is primarily controlled by the redox budget (RB) of the slab prior to subduction. Subduction-zone thermal structure, however, only exerts a minor influence on the slab-derived fluid fO2, which is supported by the similar fO2 ranges in arc lavas from cold and hot subduction zones. Our models further show that, if an open system is assumed, most of carbon (>70%) and sulfur (>50%) in cold subducted AOC and serpentinite would be lost at subarc depths. Small amounts of carbon and sulfur could be transported into the deeper mantle via closed-system subduction and open-system cold subduction, supplying the source materials for volatile-rich intraplate magmas and superdeep diamonds.